PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN KEPASTIAN HUKUM TERHADAP KINERJA PEMERINTAH DESA: THE EFFECT OF TRANSPARENCY ACCOUNTABILITY AND LEGAL CERTAINTY ON VILLAGE GOVERNMENT PERFORMANCE - Sapitri, Ade Desma; Sari, Ria Nelly; Afifah, Ulfa (Universitas Riau, 2024)
This study aims to examine the effect partially and simultaneously on the variables of accountability, transparency, and legal certainty on village government performance (study on the Village Government of Kuantan Singingi Regency). The population and sample in this study are the Village Governments of Hulu Kuantan, Central Kuantan, and Pangean Districts, totaling 48 villages. This research is a research by giving questionnaires to 3 respondents, namely the Village Head, Village Secretary, and Head of Financial Affairs so that the number of respondents in this study were 144 respondents. Data collection was carried out by distributing 144 questionnaires to 48 villages in Kuantan Singingi Regency. Determination of the sample using simple random sampling method. This study uses a multiple linear regression analysis model with SPSS 17 software. This study shows that accountability (X1) has a significant effect on village government performance, transparency X2) has a significant effect on village government performance, and legal certainty (X3) has a significant effect on village government performance. The results of testing accountability, transparency, and legal certainty simultaneously have a significant effect on village government performance.